How Advanced Is Green Participatory Budgeting in Poland and Spain? A Case Study of Gdansk and Barcelona - SIEMIONEK-RUSKAŃ, Małgorzata; SIEMIONEK-LEPCZYŃSKA, Anna (Journal of Environmental Management and Tourism, 2024)
This study explores the advancements in Green Participatory Budgeting (GPB) in Poland and Spain, focusing on case studies from Gdansk and Barcelona. GPB integrates participatory budgeting with environmental sustainability, enabling citizens to influence the allocation of municipal funds toward projects that enhance both environmental and social welfare. The research analyzes the implementation, outcomes, and challenges associated with GPB in the two cities. Spain, particularly Barcelona, has seen widespread adoption of participatory budgeting, providing valuable insights into its impact and effectiveness. The paper discusses the historical context, the evolution of participatory budgeting in these regions, and the specific green projects funded. It also highlights the environmental and social benefits, such as increased urban green spaces and enhanced community engagement, as well as the difficulties faced in achieving consensus and managing the complexities of the application process. By comparing these two cities, the study aims to shed light on the broader implications of GPB and its potential as a tool for sustainable urban development. Purpose : This study explores the advancements in Green Participatory Budgeting (GPB) in Poland and Spain, with a focus on the cities of Gdansk and Barcelona. The goal is to analyze the implementation outcomes and challenges associated with GPB, highlighting its impact on environmental and social welfare. Design/Methodology/Approach : The research employs a case study approach, examining GPB practices in Gdansk and Barcelona. Data were collected through document analysis, interviews, and direct observations conducted during the spring and summer of 2024. The study investigates the historical context, evolution, and specific green projects funded under GPB in these cities. Findings : The study reveals that Barcelona has seen widespread adoption of participatory budgeting, providing valuable insights into its effectiveness and impact. In both Gdansk and Barcelona, GPB has led to increased urban green spaces, enhanced community engagement, and significant environmental and social benefits. However, challenges such as achieving consensus and managing the complexities of the application process persist. Practical Implications: The findings suggest that GPB can be an effective tool for sustainable urban development, provided that local governments address the challenges associated with its implementation. The study offers practical recommendations for improving GPB processes, including enhanced civic education, streamlined application procedures, and continuous public outreach. Originality : This paper contributes to the understanding of GPB by comparing its implementation in two different European contexts. It provides a comprehensive analysis of GPB's potential and challenges, offering insights that can guide policymakers and practitioners in other cities considering similar initiatives.